Corruption and Productivity Growth in OECD Countries - Maria Del Mar Salinas-Jimenez; Javier Salinas-Jimenez (European Regional Science Association (ERSA), 2006)
The study of corruption is attracting lot of attention in recent years. Focusing on the economic consequences of corruption, the empirical evidence points to a positive relation between institutional integrity, or absence of corruption, and economic growth. Although most developed countries tend to have lower corruption than less developed ones, there exists significant variation within OECD countries. As an example, it may be observed that the gap in perceived corruption between the Nordic countries and southern Europe is larger than the gap between southern Europe and the average of the emerging economies. In this context, the objective of this paper is to analyze the impact of corruption on economic performance in a sample of OECD countries during the period 1980-2000. Specifically, we study the effect of corruption on productivity and efficiency change, trying to determine whether productivity growth is greater in countries with lower corruption. To this end, different productivity measures are compared by considering both output per worker and Total Factor Productivity (TFP). Furthermore, TFP change is decomposed into efficiency change and technological progress by means of Malmquist productivity indices. On the basis of this of this decomposition we will analyze whether corruption affect TFP growth via efficiency gains or technological change, thus gaining insight into the channels through which corruption influence economic growth.
Keywords: 330